The contribution of strategic management and organisational development theory, models and practice to the effectiveness of local churches : a study on a selected sample of South African urban and suburban churches at congregational level - Roux, C. H (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2005.